2016
DOI: 10.1038/scsandc.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord infarction at the level of ossification of the posterior longitudinal ligament

Abstract: INTRODUCTION:We report a case of acute tetraplegia, without any trauma or symptoms prior to onset, who presented with ossification of the posterior longitudinal ligament (OPLL) in the cervical spine with concomitant spinal cord infarction. CASE PRESENTATION: A 64-year-old man with a number of risk factors for vascular disease was admitted to our hospital with progressive motor weakness in the bilateral upper and lower extremities. He had initially felt numbness in his left upper extremity and had no previous n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is possible that DM angiopathy, therefore, interferes with nutrient delivery to other organs, including the spinal cord. Several studies mention possible spinal cord ischemia in patients with DM [18-20]. Mawad et al [21] evaluated 24 patients who developed signs and symptoms of spinal cord ischemia or infarction following thoracoabdominal aortic aneurysm surgery using MRI.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that DM angiopathy, therefore, interferes with nutrient delivery to other organs, including the spinal cord. Several studies mention possible spinal cord ischemia in patients with DM [18-20]. Mawad et al [21] evaluated 24 patients who developed signs and symptoms of spinal cord ischemia or infarction following thoracoabdominal aortic aneurysm surgery using MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 highlights the cases with OPLL that showed an acute presentation and a rapid progression. [8,5,7] In the present report, following trivial trauma, our patient presented with an acute left hemiparesis and anterior cord compression from C2 to C7 attributed to OPLL (i.e., once the brain MR ruled out a stroke).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, external mechanical compression on spinal cord may further damage blood supply of the spinal cord and further affect the functional recovery potential of the injured spinal cord. [23] The recovery potential of spinal cord artery and other compressed vessels after decompression is limited, and atherosclerosis may aggravate this pathological change, which may be one of the reasons why the recovery ratio of spinal cord function in carotid atherosclerosis group is lower than that in noncarotid atherosclerosis group. This study found that the severity of carotid atherosclerosis was not related to the postoperative recovery rate of patients with CSM.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis or plaque will result in increased vascular fragility, decreased vascular elasticity, lumen stenosis and hemodynamic changes of spinal artery, which affect blood supply to the spinal cord. In addition, external mechanical compression on spinal cord may further damage blood supply of the spinal cord and further affect the functional recovery potential of the injured spinal cord [23] . The recovery potential of spinal cord artery and other compressed vessels after decompression is limited, and atherosclerosis may aggravate this pathological change, which may be one of the reasons why the recovery ratio of spinal cord function in carotid atherosclerosis group is lower than that in noncarotid atherosclerosis group.…”
Section: Discussionmentioning
confidence: 99%